Pedagogical strategies for teaching nursing theories in undergraduate students: A scoping review protocol. - Aurélie Demagny-Warmoes; Paul Quindroit; Sébastien Colson (PLoS ONE)
From a pedagogical point of view, there is a great deal of creativity and practice in teaching conceptual models and nursing theories. However, there seems to be no synthesis of knowledge regarding the pedagogical methods used to teach them. The purpose of this scoping review is to map the available literature on the teaching of nursing conceptual models and theories in undergraduate nursing education. The scoping review will be developed in accordance with the JBI scoping review methodology and the PRISMA scoping review checklist. The aim of the results is to map the available literature data that can serve as inspiration and a foundation for the development of specific courses on conceptual models and theories in nursing sciences. This scoping review will be served as the basis for a study that will be described and explored the integration of nursing knowledge into bachelor of nursing curricula.